The effect of ambient temperature on the human blood cells (ҚазҰУ Хабаршысы. Биология сериясы, 2016)
Adaptation and extract the onslaught of external factors, the new environment is an important issue. The response to adverse environmental factors makes changes in the human body. It primarily affects greatly the immune system and the circulatory system. The regulation of body temperature in the heat is critical, because of the great potential for lethal hyperthermia.To study attended 10 local people and 10 people, who came from other regions of Kazakhstan. People create heat stress lasting 1 hour at ambient temperature + 42 - 45 ° C and 76 - 80% relative humidity once and daily for 14 days. In people of all groups was measured rectal temperature and measured changes in blood cells by method Shilling. Blood for research was taken from the vein.       The number of blood cells was determined by the standard technique with using hematology analyzer. The study set that mechanisms of regulation of body temperature on multiple high temperatures correspond to the maximum and minimum periodic rises of the body temperature. Adaptive responses to high ambient temperatures most adaptable people aged 15-18 than in aged 55-60.